Unveiling the veil of workplace Loneliness: A Theory-Concept-Methodology (TCM) framework - Choudhary, Archana; Jena, Biswa Prakash; Patre, Smruti (Psychology Hub, 2024)
The aim of the study is to learn more about the causes and effects of workplace loneliness. The study uses a TCM (Theory, Context, Methodology) framework based on various studies to critically assess and analyse the existing body of research on workplace loneliness from 2010 to 2021. This paper tries to do a comprehensive review of the antecedents, underlying processes, and outcomes, which will provide future directions for further development of the workplace loneliness construct and identify significant opportunities for researchers to advance the field's theoretical and empirical development.